Yiqi Huayu Jiedu Decoction reduces colorectal cancer liver metastasis by promoting N1 neutrophil chemotaxis - Zhou, Hua-Jian; Mu, Bai-Xiang; Wen, Meng-Chao; Zhao, Qi; Li, Yuanxiang; Zhao, Wen-Xuan; Yin, Hong-Ye; Ren, Shuai; Zhou, Jin-Yong; Chen, Min (Frontiers in Immunology, 2025)
ObjectiveTo observe the inhibitory effect and potential mechanism of Yiqi Huayu Jiedu Decoction (YHJD) on liver metastasis of colorectal cancer (CRC).MethodsWe compared the changes of liver weight and liver index before and after YHJD treatment in CRC liver metastasis mouse models. HE staining was employed to observe the pathological changes in mouse liver tissue sections. Flow cytometry was used to analyze the number and marker of neutrophils treated with YHJD. Transcriptomics, proteomics, and multiplex cytokine array analyses were conducted to further verify the role of YHJD on CXCL1. Differential gene analysis was performed to further explore the mechanism by which YHJD inhibits liver metastasis of CRC.ResultsAnimal studies demonstrated that YHJD reduces liver metastases. Flow cytometry results revealed that YHJD promotes N1 neutrophils in liver. Combining multi-omics and multiple cytokine arrays, we observed a significant increase in the expression of CXCL1 in the liver and plasma. GO and KEGG enrichment analyses indicated that YHJD may regulate the chemotaxis of neutrophils to inhibit the liver metastasis of CRC by participating in the regulation of cell adhesion molecule binding, adhesion protein binding, and multiple metabolic pathways.ConclusionsYHJD inhibits CRC liver metastasis by upregulating CXCL1, thereby promoting N1 neutrophil chemotaxis towards the liver, and concurrently raising the expression of N1 neutrophil markers.